Maldives : First Review Under the Stand-By Arrangement and the 24-Month Arrangement Under the Exogenous Shocks Facility and Requests for Waivers of Nonobservance of Performance Criteria and Modification of Performance Criterion; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Maldives. (IMF Staff Country Reports; Country Report, 2010)
The first review of Maldives' economic performance under the Stand-By Arrangement (SBA) and the Arrangement under the Exogenous Shocks Facility is discussed. The fiscal deficit in 2009 was estimated at 26u percent of GDP, 2 1\2 percentage points lower than previously projected. The growth of monetary aggregates slowed down in line with projections. A key risk concerns the ability of the government to maintain the public sector wage cuts. A negative outcome on this would have a large fiscal impact.